2017
DOI: 10.1186/s12881-017-0441-4
|View full text |Cite
|
Sign up to set email alerts
|

The susceptibility of FSHB -211G > T and FSHR G-29A, 919A > G, 2039A > G polymorphisms to men infertility: an association study and meta-analysis

Abstract: BackgroundMale infertility is a complex disorder caused by genetic, developmental, endocrine, or environmental factors as well as unknown etiology. Polymorphisms in the follicle stimulating hormone beta subunit (FSHB) (rs10835638, c.-211G > T) and follicle stimulating hormone receptor (FSHR) (rs1394205, c.-29G > A; rs6165, c.919A > G; rs6166, c.2039 A > G) genes might disturb normal spermatogenesis and affect male reproductive ability.MethodsTo further ascertain the aforementioned effects, we conducted a case-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 34 publications
1
27
1
Order By: Relevance
“…Although the frequency of allelic variants was similar between the two groups, a specific haplotype was detected more frequently in fertile men (i.e., −29G > A G allele, c.919A > G A allele, and c.2039A > G A allele) [110]. Moreover, a meta-analysis of twelve studies available in the literature confirmed that the presence of either c.919A > G G (p.T307A A) or c.2039A > G G (p.N680S S) alleles is associated to an increased risk of male infertility [110]. This result suggests that different genetic models should be considered for inferring the combinatorial contribution of FSHR SNPs in male infertility, including dominant, co-dominant, and recessive models.…”
Section: Genetic Regulation Of Fsh Action On Spermatogenesismentioning
confidence: 80%
See 4 more Smart Citations
“…Although the frequency of allelic variants was similar between the two groups, a specific haplotype was detected more frequently in fertile men (i.e., −29G > A G allele, c.919A > G A allele, and c.2039A > G A allele) [110]. Moreover, a meta-analysis of twelve studies available in the literature confirmed that the presence of either c.919A > G G (p.T307A A) or c.2039A > G G (p.N680S S) alleles is associated to an increased risk of male infertility [110]. This result suggests that different genetic models should be considered for inferring the combinatorial contribution of FSHR SNPs in male infertility, including dominant, co-dominant, and recessive models.…”
Section: Genetic Regulation Of Fsh Action On Spermatogenesismentioning
confidence: 80%
“…Therefore, the combination of SNPs modulating the FSHR and FSHB gene transcription and receptor functioning may be predictive of the gonadal response to the hormone in vivo. A recent case-control study evaluated three FSHR SNPs (c.919A > G, c.2039A > G, and c.−29G > A) in 255 infertile men and 340 healthy controls [110]. Although the frequency of allelic variants was similar between the two groups, a specific haplotype was detected more frequently in fertile men (i.e., −29G > A G allele, c.919A > G A allele, and c.2039A > G A allele) [110].…”
Section: Genetic Regulation Of Fsh Action On Spermatogenesismentioning
confidence: 99%
See 3 more Smart Citations